Estimates for the Approximations of the Classes of Analytic Functions by Interpolation Analogs of the De-La-Vallée–Poussin Sums - Voitovych, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We establish two-sided estimates for the exact upper bounds of approximations by the interpolation analogs of the de-la-Vallée-Poussin sums on the classes of 2π -periodic functions C β,s ψ specified by the sequences ψ(k) and shifts of the argument β , β ∈ ℝ, under the condition that the sequences ψ(k) satisfy the d’Alembert D q , q ∈ (0, 1), condition. Similar estimates are obtained for the classes C β ψ H ω generated by convex moduli of continuity ω(t). Under the conditions n − p → ∞ and p → ∞, the indicated estimates turn into asymptotic equalities.